2004
DOI: 10.1111/j.1600-0404.2004.00274.x
|View full text |Cite
|
Sign up to set email alerts
|

High mortality of subjects with endemic ataxic polyneuropathy in Nigeria

Abstract: This study shows that endemic ataxic polyneuropathy decreases survival. The finding of lower risk of death in the community with higher exposure to cyanide from cassava foods indicates that mortality of endemic ataxic polyneuropathy is not associated with exposure to cyanide from cassava foods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…The duration of fermentation of cassava mash has been shown to influence the level of cyanogenic compounds in gari, although contrary to popular notion a long duration of fermentation is not associated with a low level of cyanogenic compounds. 42,44 More cassava processors in the southeastern area added palm oil to their gari than did processors in other geographical areas. Processors attributed addition of palm oil to demands of consumers.…”
Section: Methods Of Processing Cassava To Gari In Geographical Areasmentioning
confidence: 99%
See 2 more Smart Citations
“…The duration of fermentation of cassava mash has been shown to influence the level of cyanogenic compounds in gari, although contrary to popular notion a long duration of fermentation is not associated with a low level of cyanogenic compounds. 42,44 More cassava processors in the southeastern area added palm oil to their gari than did processors in other geographical areas. Processors attributed addition of palm oil to demands of consumers.…”
Section: Methods Of Processing Cassava To Gari In Geographical Areasmentioning
confidence: 99%
“…39,42 Studies have shown that levels of residual cyanogens in cassava foods vary depending on the method of processing used to produce the food. 32,42,43 A study in Cameroon showed that gari containing similar levels of residual cyanogens can be produced from cassava varieties containing different levels of cyanogenic compounds, 40 while a study in Nigeria showed that the same variety of cassava can be processed to different gari containing varying levels of cyanogenic compounds. 44 These studies suggest that the method of processing is the major determinant of the level of residual cyanogens in cassava food.…”
Section: Cyanogenic Compounds In Garimentioning
confidence: 99%
See 1 more Smart Citation
“…Screening for enteroviruses and arboviruses in any child with flaccid paralysis is essential. Acquired conditions seen in other parts of Africa include sickle cell-related sensory neuropathy [37], leprosy-related neuropathy [38], the paralytic form of rabies [39], diphtheria and an ataxic polyneuropathy from Nigeria [40]. Sickle cell disease is prevalent throughout Africa.…”
Section: Recognition Of Etiologiesmentioning
confidence: 99%
“…Clinical syndromes, which include ataxic polyneuropathy (Monekosso & Annan, 1964;Oluwole et al, 2000), konzo (Ministry of Health Mozambique, 1984), endemic goitre (Nwokolo et al, 1966), diabetes mellitus (Pitchumoni et al, 1988) and endomyocardial fibrosis (Davies, 1990), have been attributed to exposure to cyanide from cassava foods. All cultivars of cassava, Manihot esculenta Crantz, have been shown to contain cyanogenic glycosides (Bokanga, 1994;Rogers, 1963), which are reduced during processing of cassava to products like flours, pastes and granules (Nambisan, 1994;Oluwole, 2002). Cyanogenic glycosides are usually present in these products due to inefficiencies of the methods of processing (Oduro et al, 2000;Oluwole et al, 2002b).…”
Section: Introductionmentioning
confidence: 99%